2016
DOI: 10.3389/fpsyg.2016.01775
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness from Emotion Fit: Emotional Frame, Consumer Emotion, and Feeling-Right in Consumer Decision to Forgive

Abstract: Three studies examine an emotion fit effect in the crisis communication, namely, the interaction between emotional frames of guilt and shame and consumer emotions of anger and fear on consumer forgiveness. Guilt-framing communication results in higher forgiveness than shame-framing for angry consumers, whereas shame-framing communication results in higher forgiveness than guilt-framing for fearful consumers. These effects are driven by consumers' accessible regulatory foci associated with anger/fear and guilt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…Findings in social psychology also support our assumption. Individuals are more likely to feel extremely offended when they are criticized by a group they are strongly attached to (Moreland and McMinn, 1999) or by a transgressor with whom they perceive they have a quality relationship (McCullough et al, 1998). Further, for highly identified firms, negative information drives consumers to feel betrayed and to react strongly in a more permanent way (Bhattacharya and Sen, 2003).…”
Section: Perceived Betrayal As the Underlying Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings in social psychology also support our assumption. Individuals are more likely to feel extremely offended when they are criticized by a group they are strongly attached to (Moreland and McMinn, 1999) or by a transgressor with whom they perceive they have a quality relationship (McCullough et al, 1998). Further, for highly identified firms, negative information drives consumers to feel betrayed and to react strongly in a more permanent way (Bhattacharya and Sen, 2003).…”
Section: Perceived Betrayal As the Underlying Mechanismmentioning
confidence: 99%
“…The aforementioned moderating role of brand biography and the transgression types with a boundary condition were all replicated in the integrated model of Study 4. Thus, the type of brand transgression in which the underdog is involved may be critical, but how to categorize the transgression and communicate the nature of such transgressions to the consumers may be a more crucial factor in altering consumer attitudes toward the related brands (Ran et al, 2016).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Moreover, during the tasting of the dishes, the diner mainly focuses on looking at the dish he is tasting, especially on those dishes in which the dish must be interacted with. From the application of traditional marketing (in-depth interview), it can be highlighted that the experience was generally valued by all as very good and enriching in both phases, since satisfied consumers consider their expectations met (Ran et al, 2016). However, consumers are delighted when they have lived an experience that meets their expectations (Martínez-Ruiz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, though we demonstrated the mediating role of temporal perspective in the current research (studies 2 and 3), there are other potential factors that could have influenced the confirmed effects as well. For example, could promotion or prevention orientation drive consumers to highlight reaping rewards or avoiding punishments (Ran et al, 2016)? Examining how exactly the above processes work also seems to be a fertile ground for subsequent research.…”
Section: Discussionmentioning
confidence: 99%